Best (boy)friend forever - Morgan, Melissa J. (New York : Grosset & Dunlap, 2006)
During her third year at Camp Lakeview, resident tomboy Priya finds that being best friends with a boy has some drawbacks now that they are both growing up.
Keywords: Camps -- Juvenile fiction; Best friends -- Juvenile fiction; Friendship -- Juvenile fiction; Interpersonal relations -- Juvenile fiction; Camps -- Fiction; Best friends -- Fiction; Friendship -- Fiction; Interpersonal relations -- Fiction